PENGARUH PENGELUARAN KONSUMSI RUMAH TANGGA, PENGELUARAN PEMERINTAH TERHADAP PENYERAPAN TENAGA KERJA SERTA PERTUMBUHAN EKONOMI BALI - Martaningsih D, Anak Agung Fitri; Marhaeni, A.A.I.N (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Economic growth is development goal of every region, including the Regency / City of Bali. In order for this to be achieved, it requires the participation of the government in maintaining national stability. The purpose this study 1) analyze effect of household consumption expenditure and government expenditure on labor absorption in the regencies / cities of Bali Province; 2) analyze effect of household consumption expenditure, government expenditure, and labor absorption on economic growth in the regencies / cities of Bali Province; 3) analyze role of labor absorption in mediating the effect of household consumption expenditure and government expenditure on economic growth in the regencies / cities of Bali Province. Using secondary data, 81 observations with descriptive statistical analysis and path analysis. Results are 1) household consumption expenditure and government expenditure directly have a significant positive effect on employment in the regencies / municipalities of Bali Province; 2) household consumption expenditure and government expenditure do not directly affect economic growth, while employment has a significant positive effect on economic growth; 3) labor absorption mediates the effect of household consumption expenditure and government expenditure on economic growth in the regencies / cities of Bali Province. Keywords: economic growth, employment, consumption, government spending